Pengembangan Kurikulum Pendidikan Seksual siswa Pra Pubertas Sekolah Dasar: Systematic Literature Review - Humamy, Raudhoh Fitra; Kamelia, Alfina; Ali, Mahrus; Wicaksono, Dirgantara (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Pre-puberty age of elementary students grade 4-6 is a transitional age where children started to be attracted to the opposite sex and experience puberty. Unfortunately, lack of sexual education awareness remains a problem among parents, the school environment and the community nowadays. This results in children’s lack of understanding towards their body changes, healthy relationships, and self-protection ability. Increase the risk for them being exposed with sexual violence and misinformation. This article aims to analyze the development of a sexual education curriculum for pre-pubertal elementary school students using a Systematic Literature Review (SLR) approach. Sexual education at an early age is a preventative effort to shape healthy understanding, attitudes, and behaviors related to reproduction, the body, and social interactions that align with moral and religious values. This research methodology uses systematic literature review by searching, selecting, analyzing and synthesizing articles under inclusion criteria that is published between 2015-2025 through reputable databases. The result shows that the curriculum development of sexual education for pre-pubertal students emphasizes more on the body anatomy, personal hygiene, interaction boundaries for opposite sex, as well as instilling the politeness and self-protection from sexual violence and harrasment and values. Holistic approach based curriculum, which combines cognitive, affective and psychomotor aspects is considered effective in improving sexual literacy of children. Support from teachers, parents, and school policies are highly required. This study recommends the need of curriculum design which is sensitive to culture and religion context as well as teacher training for appropriate learning implementation. Further research is expected to develop a comprehensive character-focused curriculum model